Laser surface modification of AISI 1025 steel - Nik Nadia Farhana, Nik Zulkifli (2013)
Low carbon steels tends to fail due to high wear applications. This project focused on laser surface modification of AISI 1023 steel to improve surface hardness properties. In this project, Nd:YAG laser JK300HPS was used to modify the surface on substrate surface. Three set parameters which of laser power, pulse duration and overlap percentage were set as respective range of 1700 to 2500 W, 0.7 to 1.0 ms and 0 to 50%. The characterization for treated samples was conducted for hardness test and metallographic study. Hardness test were carried out by using Vickers indenter with Hv0.1. Optica microscope was used to study the depth of treated sample for metallographic study. From the findings, lower speed produced higher hardness of 461 Hv 0.1. The hardness result that obtained from the study increased 300 % from the substrate region. The depth of modified layer ranged between 50 and 400 µm. These findings were important for structural material design.